HUBUNGAN ANTARA PENDIDIKAN DAN PEKERJAAN IBU DENGAN KEJADIAN DIARE PADA BALITA DI PUSKESMAS BASUKI RAHMAT PALEMBANG TAHUN 2011 - Rini Mayasari Rini Mayasari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2012)
ABSTRACT According to the health of the World Health Organization (WHO) in poor countries and developing countries, mortality in infants and young children from diarrhea about two million children each year, the purpose of this study was to determine the relationship between education and employment to women with the incidence of diarrhea in children in health centers in 2011 Pelembang Basuki Rahmat This study uses survey Cross sectional analytic approach. The population in this study were all mothers who have young children who come to visit the health center Palembang Basuki Rahmat which amounts to 448 people and a random sample random sampling. Variable that is examined in the analysis using univariate and bivariate analysis via Chi-Square test at α = 0.05. The results of univariate analysis showed that mothers who have children diagnosed with diarrhea as many as 94 people (65.7%) and diarrhea are not diagnosed in 49 men (34.3%), mothers with higher education as many as 68 people (47.6%) and low education as many as 75 people (52.4 %) and mothers who worked as many as 91 people (63.6%) and that does not work as many as 52 people (36.4%). The results of bivariate analysis showed that the incidence of diarrhea in toddlers higher education less mothers were 36 (52.9%) compared with the incidence of diarrhea in children with poorly educated mothers as much as 58 (77.3%), the incidence of diarrhea in infants whose mothers work as much as 72 larger (79.1 %) compared with the non-occurrence of diarrhea in infants whose mothers worked were 19 (20.9%). chi-square test showed no significant association between education with incidence of diarrhea (p value = 0.004) and there was a significant association between maternal work (p value = 0.000) with the incidence of diarrhea in health centers Basuki Rahmat Palembang in 2011. Expected to health workers in order to improve health services, especially education about risk factors for the incidence of diarrhea in infants. ABSTRAK 21 Menurut badan kesehatan world health organization (WHO) di negara negara miskin dan sedang berkembang, kematian pada bayi dan anak anak akibat diare berkisar dua juta anak tiap tahunnya tujuan penelitian ini adalah untuk mengetahui hubungan antara pendidikan dan pekerjaan ibu dengan kejadian diare pada balita di puskesmas basuki rahmat pelembang tahun 2011. Penelitian ini menggunakan metode survey analitik dengan pendekatan Cross Sectional. Populasi dalam penelitian ini adalah semua ibu yang mempunyai anak balita yang datang berkunjung ke puskesmas basuki rahmat Palembang yang berjumlah 448 orang dan pengambilan sampel secara random sampling. Variable yang di teliti di analisis dengan menggunakan analisis univariat dan bivariat melalui uji Chi-Square pada α = 0,05. Hasil analisis univariat menunjukkan ibu yang memiliki balita yang terdiagnosa diare sebanyak 94 orang (65.7%) dan yang tidak terdiagnosa diare sebanyak 49 orang ( 34.3%), ibu dengan pendidikan tinggi sebanyak 68 orang (47.6%) dan pendidikan rendah sebanyak 75 orang (52.4%) dan ibu yang bekerja sebanyak 91 orang (63.6%) dan yang tidak bekerja sebanyak 52 orang (36.4%). Hasil analisis bivariat menunjukkan kejadian diare pada balita yang pendidikan ibunya tinggi lebih kecil sebanyak 36 (52.9%) dibandingkan dengan terjadinya diare pada balita dengan ibu berpendidikan rendah sebanyak 58 (77.3%), kejadian diare pada balita yang ibunya bekerja lebih besar sebanyak 72 (79.1%) dibandingkan dengan tidak terjadinya diare pada balita yang ibunya bekerja sebanyak 19 (20.9%). uji chi-square menunjukkan ada hubungan yang bermakna antara pendidikan dengan kejadian diare ( p value = 0,004) dan ada hubungan yang bermakna antara pekerjaan ibu (p value =0,000) dengan kejadian diare di Puskesmas Basuki Rahmat Palembang tahun 2011. Diharapkan kepada petugas kesehatan agar dapat meningkatkan pelayanan kesehatan terutama penyuluhan tentang faktor resiko kejadian diare pada balita.